Tradability and the Labor‐Market Impact of Immigration: Theory and Evidence From the United States. Issue 3 (8th May 2020) - Burstein, Ariel; Hanson, Gordon; Tian, Lin; Vogel, Jonathan
Abstract : In this paper, we study how occupation (or industry) tradability shapes local labor‐market adjustment to immigration. Theoretically, we derive a simple condition under which the arrival of foreign‐born labor into a region crowds native‐born workers out of (or into) immigrant‐intensive jobs, thus lowering (or raising) relative wages in these occupations, and we explain why this process differs within tradable versus within nontradable activities. Using data for U.S. commuting zones over the period 1980–2012, we find—consistent with our theory—that a local influx of immigrants crowds out employment of native‐born workers in more relative to less immigrant‐intensive nontradable jobs, but has no such effect across tradable occupations. Further analysis of occupation labor payments is consistent with adjustment to immigration within tradables occurring more through changes in output (versus changes in prices) when compared to adjustment within nontradables, thereby confirming our model's theoretical mechanism. We then use the model to explore the quantitative consequences of counterfactual changes in U.S. immigration on real wages at the occupation and region level.